2018
DOI: 10.1210/en.2018-00769
|View full text |Cite
|
Sign up to set email alerts
|

The Adrenal Clock Prevents Aberrant Light-Induced Alterations in Circadian Glucocorticoid Rhythms

Abstract: The glucocorticoid (GC) rhythm is entrained to light-dark (LD) cycles via a molecular clock in the suprachiasmatic nucleus (SCN) and is maintained by an adrenal clock synchronized by SCN-dependent signals. Targeted deletion of the core clock gene Bmal1 can disrupt adrenal clock function. The requirement of the adrenal clock to stabilize the circadian GC rhythm during exposure to aberrant LD cycles was determined using novel aldosterone synthase (AS)Cre/+::Bmal1Fl/Fl mice in which Bmal1 deletion occurred during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…This sexually dimorphic response could partly be explained by the unequal hM3Dq expression at 20 weeks of age in males and females ( Figure 1B). Notably, previous mouse models that have used the AS-Cre mouse line to drive adrenal cortex-specific Cre expression have exhibited similar sex differences (49,50).…”
Section: Resultsmentioning
confidence: 99%
“…This sexually dimorphic response could partly be explained by the unequal hM3Dq expression at 20 weeks of age in males and females ( Figure 1B). Notably, previous mouse models that have used the AS-Cre mouse line to drive adrenal cortex-specific Cre expression have exhibited similar sex differences (49,50).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, melatonin seems to directly inhibit ACTHstimulated steroidogenesis (Campino et al 2011). In mice with a selective knockout of Bmal in the adrenocortical cell, basal steroidogenesis and stress-induced response were maintained (Dumbell et al 2016), albeit with an exaggerated response, especially in females, and the animals were more vulnerable to light-induced timeshift, suggesting that the adrenal clock machinery acts to buffer steroidogenic responses and stabilize circadian glucocorticoid rhythmicity (Engeland et al 2018(Engeland et al , 2019.…”
Section: Hypercortisolism and Adrenocortical Tumorsmentioning
confidence: 99%
“…In turn, GR activity can be regulated by clock proteins, including CLOCK and Cryptochrome 1 and 2 (Cry1 and Cry2) (Nader et al, 2009;Lamia et al, 2011) via non-genomic mechanisms. With regard to a link between clock genes and adrenal steroidogenic pathways, studies in mice have shown that the expression of StAR is regulated by the activity of the CLOCK-BMAL complex (Son et al, 2008;Leliavski et al, 2014) and mutation in the Bmal gene in the adrenal gland leads to loss of corticosterone circadian rhythm in mice housed in altered light cycle (Son et al, 2008;Engeland et al, 2018). In light of this, we hypothesised that the changes in the expression of steroidogenic genes observed in MP-T and in MP-W rats may be associated with changes in adrenal clock genes expression.…”
Section: Mpred Affects the Expression Of Adrenal Clock Genesmentioning
confidence: 99%